Intra Arterial Tirofiban in the Peri Operative Priming for Intracranial Stent Deployment in Aneurysms – A cross Sectional Study - Manjooran, Kavitha Raju; Palatty, Princy Louis; Ramachandran, Sreehari Nirmal; Menon, Sajesh Karunakara (Nepal Journal of Neuroscience, 2024)
Introduction: Tirofiban is a glycoprotein IIb/IIIa receptor antagonist that inhibits platelet aggregation. Primary and secondary objectives of this study were to determine the efficacy and to determine the safety profile of intra arterial tirofiban in the peri operative priming for intracranial stent deployment in aneurysms respectively. Materials and methods: This was a cross sectional study in a tertiary care centre in Kerala. Patient admitted with sub arachnoid haemorrhage/aneurysm posted for endovascular stent associated procedures and willing for the study were selected. The pre procedure assessment of neurological status was done. Patient underwent the procedure where peri operative priming with intraarterial tirofiban was given. The development of any neurological deficits within 24 hours was assessed using Glasgow coma scale and National Institute Health Stroke Scale. Laboratory blood parameters before and after procedure were also reviewed. Results: Study involved 58 patients with aneurysm who were given intraarterial tirofiban. No significant difference (p value 0.521) in Glasgow coma scale on admission (14.89 ± 0.462) and on discharge (14.74 ±1.650). Analysis was done using SPSS version 20.00. Paired samples T test and Wilcoxon Signed Rank Test were used. Conclusion: Results showed that intra arterial tirofiban is effective and the procedure was uneventful with no complications. Patients recovered well and the hospital stay was of minimum duration.